Key Elasticities in Job Search Theory : International Evidence - John T. Addison; Mário Centeno; Pedro Portugal (Institute for the Study of Labor (IZA), 2004)
This paper exploits the informational value of search theory, after Lancaster and Chesher (1983), in conjunction with survey data on the unemployed to calculate key reservation wage and duration elasticities for most EU-15 nations.
Keywords: J64; J65; 330; reservation wages; probability of reemployment; accepted wages; unemployment benefits; Pareto wage offer distribution; Arbeitsplatzsuchmodell; Anspruchslohn; Berufliche Integration; Arbeitslosenversicherung; Elastizität; Theorie; EU-Staaten